Urban Political Ecologies and Children's Geographies: Queering Urban Ecologies of Childhood. (22nd April 2016) - Shillington, Laura J.; Murnaghan, Ann Marie F.
Abstract: This article focuses on the material and discursive constructions of nature and children in the city. While dominant representations and idealizations of nature and childhood depend on the binary logic of the nature/culture and rural/urban divide, there is also a simplification and romanticization of nature in children's geographies and a lack of children and their spaces in urban political ecology. We argue that children and nature in cities need to be removed from a binary model of being and attended to in more nuanced ways in urban political ecology and children's geographies. In this regard, we suggest that both nature and children in cities need to be queered. We need to ask how the production of urban spaces (re)creates particular romantic and idealized relations with natures that reify the binaries between nature/culture, and male/female through a heteronormative framework. The purpose of this article is to bring the critical nature–society theories of urban political ecology into conversation with work in children's geographies that explores the 'nature' of childhood, and in doing so queer the relationship between children and nature. Drawing on research on queer ecologies, and queered childhoods, we aim to provide a framework to rethink and queer both nature and children in cities.